Analysis of Credit Guarantee Binding with Power of Attorney to Enforce Mortgage Rights - Nadya Apriliani; Kristi Warista Simanjuntak (Faculty of Law, Universitas Muhammadiyah Sorong, 2024)
This study aims to determine the legal consequences of binding credit collateral with a Power of Attorney to Enforce Mortgage Rights (SKMHT) and to find out the legal remedies that can be taken by creditors against collateral bound by SKMHT if the debtor defaults. This research was conducted using juridical-normative research with data obtained from legal materials and library materials which were then analyzed using qualitative methods. The results obtained from this research include, among others, the encumbrance of Mortgage Rights through SKMHT must be upgraded to APHT in accordance with the laws and regulations. If it is not done, the SKMHT is declared null and void and the creditor's position is not as a preferred creditor who has the right to execute the collateral object if the debtor defaults, but there are exceptions to the type of micro business credit binding that is classified as productive in Ministerial Regulation Number 22 of 2017, while the legal efforts that can be taken by creditors through litigation and non-litigation channels to obtain a legally enforceable judge's decision to be able to carry out the execution or sale process under the hands of the creditor